Directionally compensated mechanical work provided by the shoulder leads to similar racket velocities during open and square stance forehand groundstrokes in tennis - Kawamoto, Y.; Iino, Y.; Yoshioka, S.; Fukashiro, S. (European Journal of Sport Science, 2019)
The differences between the racket-arm acceleration mechanisms during open and square stance forehand groundstrokes in tennis were examined by quantifying the mechanical work done on the racket arm. We studied 13 advanced tennis players as they performed these strokes at maximum effort and calculated the work using inverse dynamics. The racket head speed was similar between the open and square stances. In the open stance, the lack of weight shifting towards the hitting direction resulted in a lower velocity for the shoulder joint centre in the hitting direction than in the square stance, and less work was done by the shoulder joint force in the hitting direction in the open stance than in the square stance (0.30 ± 0.11 J·kg-1 vs. 0.38 ± 0.16 J·kg-1; p = 0.005). However, in the open stance, the torso rotated more towards the hitting direction and had more upward acceleration, which resulted in more work done by the sideways and upward shoulder joint forces than in the square stance (sideways: 0.07 ± 0.09 J·kg-1 vs. 0.05 ± 0.09 J·kg-1, p = 0.046; upward: 0.08 ± 0.09 J·kg-1 vs. 0.04 ± 0.07 J·kg-1, p = 0.002). Thus, the greater work done by the sideways and upward shoulder joint forces compensated for the lesser work done by the shoulder joint force in the hitting direction in the open stance. In both stances, mainly the horizontal flexion torque and internal rotation torque at the shoulder increased the energy of the racket arm.